AB0513 Fatigue in chinese patients with primary sjÖgren's syndrome: a cross sectional study. (15th June 2017) - Li, L; Cui, Y; Chen, S; Zhao, Q; Li, L; Gu, Z
Abstract : Background: Primary Sjögren's syndrome (pSS) is the second most common systemic autoimmune disease, with a female-male ratio of 9:1, and characterized by sicca symptoms of the eyes and mouth, including joint pains and multi-system involvement. pSS affects patients' health-related quality of life (QoL), mental status and relationships with family. In pSS patients, symptoms such as fatigue, depression, arthralgia, fibromyalgia and general loss of well-being are commonly reported. Among them, fatigue is the most common problem that includes physical and mental fatigue, it can be as disabling as pain, which is difficult to manage and has a notable impact on QoL. Fatigue is a tiredness which may be mental, physical, or both, and that results in an inability to function at normal performance levels. However, the underlying pathophysiological mechanisms of fatigue remain unclear. A number of studies have reported the association of fatigue with Primary Sjögren's syndrome (pSS), whereas, because of the small sample size of pSS patients, we still lack large sample studies to find the relationship between pSS and fatigue. Objectives: To investigate the relationship of fatigue severity to other clinical features in primary Sjögren's syndrome (pSS) and to identify factors contributing to the physical and mental aspects of fatigue in Chinese patients. Methods: Sixty-seven consecutive patients with PSS according to the American-European Consensus group (AEGG) criteria were included. Demographic, clinical and biological characteristics for all patients were collected. The Fatigue Severity Scale (FSS), Profile of Fatigue (ProF), Visual analogue scale, Hospital Anxiety and Depression Scale (HADS), OHIP-14 Scale, MDADI Scale and PSQI Scale were adopted to assess fatigue, depression, anxiety, xerostomia, xerophthalmia and sleep disturbances. Associations with fatigue were compared using multivariate regression. Results: 94% of our patients were women. The mean age of patients was 51.13±13.23 years, and the mean disease duration was 4.12±4.49 years. The mean oral dryness was 51±17.82, and the mean ocular dryness was 33.56±26.3. Abnormal fatigue, defined as an FSS score >or=4, was present in 64% of the patients. Dry symptoms, low educational level, Pain and depression had a negative impact on fatigue scores. The regression models explained that Pain and depression were the strongest predictors of fatigue according to the FSS. Conclusions: Fatigue is a tiredness which may be mental, physical, or both, and that results in an inability to function at normal performance levels. However, the underlying pathophysiological mechanisms of fatigue remain unclear. From our study, we found that psychosocial variables are determinants of fatigue, and fatigue is associated with depression, but depression is not the primary cause of fatigue in primary SS. Therefore, the investigation of the pathophysiologic correlates of physical and mental aspects of fatigue is needed to guide the development of more effective interventions. Acknowledgements: This study was supported by National Natural Science Foundation of China (81401124);the Collaborative Innovation Program of Affiliated Hospital of Nantong University; College graduate research and innovation of Jiangsu Province (KYZZ16–0358, KYZZ15–0353). Disclosure of Interest: None declared